Rules of the cataloguing standard Resource Description and Access that may be standardized in library catalog - Faria, Cleide Vieira de (2019)
Resource Description and Access (RDA) is the cataloging standard that was released in 2010 to replace the AACR2. Configuring some RDA rules requires local decisions from the cataloging agency or allows options, choices, and cataloger judgment. This aspect of the norm directs towards the elaboration of the cataloging policy to implement the RDA. The present study questions which are the RDA rules that can be standardized in the cataloging policy of the library. In it, bibliographic research was used on primary and secondary sources on the standard and was limited to analyzing 17 RDA rules. The results considered that the rules – Language and Script; RDA Elements; Sources of Information; Capitalization; Punctuation; Abbreviations; Recording Statement of Responsibility; Statement of Responsibility Relating to Title Proper; Statement Naming More Than One Agent; Extent (Exact Number of Units Not Readily Ascertainable; Single Volume with Unnumbered Pages, Leaves, or Columns) ; Content Type; Media Type; Carrier Type - are prone to be discussed in the cataloging policy of the library. The rules of the RDA - Changes Requiring a New Description; Inaccuracies; ISBD Punctuation; Recording Edition Statement; Publication Statement e Place of Publication Not Identified in the Manifestation - were considered not prone to standardization in the cataloging policy and should be followed as directed by the RDA. It is concluded that the cataloging policy is an important document, being essential for the cataloging with the RDA.